Is it time for libraries to take a closer look at emoji? The data deluge column. Issue 5 (4th July 2018) - Frederick, Donna Ellen
Abstract : Purpose: The emoji, is it an endearing image to add to your text messages and email, or is it an increasingly important type of electronic data? According to a 2013 article by Jeff Blagdon, the idea of using some sort of symbol in electronic communication has been with us for about two decades. Japanese in origin, the earliest symbols of this type were developed in the era of pagers and old-style cell phones and were commonly called emoticons. Design/methodology/approach: As devices developed a greater capacity to display graphical elements these keystroke representations were replaced with Unicode characters which display on our electronic devices, which we now call emoji. This instalment of the data deluge will look at the emoji as a form of data and explore how and why their ubiquity may create new opportunities for libraries. Findings: Some readers, as well as the author of this column, may be tempted to scoff at the idea that the emoji is anything more than a form of shorthand for use in electronic communications or cutesy decorations. Originality/value: One night she showed up at the class, and the instructor wrote on the board, "Computers in school libraries: A new tool or a flash in the pan?" He went on to warn school librarians to not be dazed by this "new computer phase" which he felt distracted both teachers and students from the real work of teaching and learning. He felt that if there were computers in schools, they only belonged in the mathematics classroom and that, even in that context, they only had limited application.